Fiber Bragg Based Sensors for Foot Plantar Pressure Analysis - Leal-Junior, Arnaldo G.; Domingues, Maria F.; Vilarinho, Débora; Theodosiou, Antreas; Tavares, Cátia; Alberto, Nélia; Leitão, Cátia; Kalli, Kyriacos; Frizera-Neto, Anselmo; André, Paulo; Antunes, Paulo; Marques, Carlos Alberto F. (My University, 2019)
Gait analysis is of major importance in physical rehabilitation scenarios, lower limbs diseases diagnosis and prevention. Foot plantar pressure is a key parameter in the gait analysis and its dynamic monitoring is crucial for an accurate assessment of gait related pathologies and/or rehabilitation status evolution. It is therefore critical to invest effort in research for foot plantar analysis technologies. From that perspective, optical fiber sensors appear to be an excellent solution, given their sensing advantages for medical applications, when compared with their electronic counterparts. This chapter explores the use of optical fiber Bragg grating (FBG) sensors, both in plastic and silica optical fiber, to dynamically monitor the foot plantar pressure. An array of FBGs was integrated in a specially designed cork insole, with the optical sensors placed at key pressure points for analysis. Both insoles, containing plastic and silica optical fiber sensors, were tested for dynamic gait monitoring and body center of mass displacement, showing the reliability of this sensing technology for foot plantar pressure monitoring during gait motion.
Keywords: Fiber; Fiber Bragg Gratings; Foot plantar pressure; Gait analysis; Polymer optical; Silica optical fiber